Clodronate: The Influence on ATP Purinergic Signaling - Rosini, Sergio; Rosini, Stefano; Saviola, Gianantonio; Molfetta, Luigi (Current Rheumatology Reviews, 2026)
ATP is involved in numerous physiological functions, such as neurotransmission, modulation, and secretion, as well as in cell proliferation, differentiation, and death. While ATP serves an essential intracellular role as a source of energy, it behaves differently in the extracellular environment, where it acts as a signaling molecule capable of activating specific purinergic receptors (P2YRs and P2XRs) that modulate the response to ATP. Extracellular ATP signaling is a dynamic area of research, with particular interest in ATP’s effects on inflammatory conditions and pain modulation. Clodronate differs from other bisphosphonates that contain an amino group in their structure (N-BPs), and it is metabolized within osteoclasts into a toxic ATP analog, AppCCl2p, which causes mitochondrial dysfunction and osteoclast apoptosis. This characteristic differentiates Clodronate from N-BPs, as the latters act by interfering with the mevalonate pathway. Clodronate has demonstrated anti-inflammatory and analgesic activity in various bone and musculoskeletal diseases through mechanisms involving macrophages, neutrophils, peripheral nociceptors, and the central nervous system. ATP produced inside cells is accumulated within transport vesicles, where it penetrates via a VNUT channel and is then released extracellularly, playing an active role in acute and chronic inflammatory processes, neurotransmission of pain, and liver disease regulation. Clodronate influences these processes due to its strong inhibitory effect on VNUT-mediated ATP release. The aim of this review is to highlight the therapeutic potential offered by appropriate modulation of cellular ATP release and the inhibitory effects of Clodronate on the channel through which ATP penetrates transport vesicles.
Keywords: Clodronate